2005
DOI: 10.12968/denu.2005.32.1.16
|View full text |Cite
|
Sign up to set email alerts
|

To Open or to Close Space – That is the Missing Lateral Incisor Question

Abstract: Developmentally absent permanent maxillary lateral incisors may be associated with several problems. The decision whether to open or to close the space should involve the patient/parent, orthodontist and restorative dentist. To optimize function and aesthetics, space should be opened using fixed appliances to accommodate an appropriate prosthesis. Implant-retained crowns offer several advantages, although adhesive bridges are more appropriate in certain circumstances. Removable partial dentures may be necessar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
2
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 0 publications
0
21
2
1
Order By: Relevance
“…Comparing the results from published narrative reviews with the results obtained from the present systematic review, no agreement between the conclusions was found .…”
Section: Discussioncontrasting
confidence: 66%
“…Comparing the results from published narrative reviews with the results obtained from the present systematic review, no agreement between the conclusions was found .…”
Section: Discussioncontrasting
confidence: 66%
“…It is an essential asset for psychosocial adaptation, people with beautiful teeth and smiles are considered more attractive, more intelligent and more popular with the opposite gender . The clinical examination reveals a variety of esthetic problems such as unpleasant space between teeth as well as deviation of the midline to the affected site (in unilateral case) in the case of hypodontia or microdontia or teeth crowding in macrodontia . The supernumerary teeth may cause impaction of the adjacent tooth …”
Section: Discussionmentioning
confidence: 99%
“…[79] Therefore, it was decided to use space obtained by extracting questionable maxillary right central incisor for orthodontic purpose and also in this case sacrificing the pathology free healthy premolar is invariably an excessive biological cost for a modest functional and aesthetic gain. [10] Following considerations were address while substituting canine as lateral incisor and first premolar as canine (1) parallel or slightly over upright the roots of the lateral incisors towards midline (2) lingually torque the canine roots to reduce canine prominence of the canine eminence (3) rotate the first premolar mesiopalatally to give them a more canine–like appearance and to conceal lingual cusp. [11] Thordarson et al .…”
Section: Discussionmentioning
confidence: 99%